2020
DOI: 10.1002/ijc.32813
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of RAS alterations in diverse malignancies and impact of targeted therapies

Abstract: RAS alterations are often found in difficult-to-treat malignancies and are considered "undruggable." To better understand the clinical correlates and coaltered genes of RAS alterations, we used targeted next-generation sequencing (NGS) to analyze 1,937 patients with diverse cancers. Overall, 20.9% of cancers (405/1,937) harbored RAS alterations. Most RAS-altered cases had genomic coalterations (95.3%, median: 3, range: 0-51), often involving genes implicated in oncogenic signals: PI3K pathway (31.4% of 405 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
(114 reference statements)
0
21
0
Order By: Relevance
“…The molecular mechanisms underlying this exceptional response were elucidated by in vitro modeling that demonstrated that the known partial agonist/antagonist mechanism of tamoxifen compared with the estrogen depletion of letrozole was likely the critical feature that explained the different responses to the combination of each agent with an MEK inhibitor. It has previously been suggested that customized combination therapy may be a key to achieving tumor control when there are important genomic co‐alterations [9, 10], especially when certain gene product pathways, such as KRAS or PI3K, are activated [22]. Our current observations indicate that drugs with subtly different mechanisms of action targeting the same receptor may have markedly different anticancer activity when used in combinations.…”
Section: Discussionmentioning
confidence: 62%
“…The molecular mechanisms underlying this exceptional response were elucidated by in vitro modeling that demonstrated that the known partial agonist/antagonist mechanism of tamoxifen compared with the estrogen depletion of letrozole was likely the critical feature that explained the different responses to the combination of each agent with an MEK inhibitor. It has previously been suggested that customized combination therapy may be a key to achieving tumor control when there are important genomic co‐alterations [9, 10], especially when certain gene product pathways, such as KRAS or PI3K, are activated [22]. Our current observations indicate that drugs with subtly different mechanisms of action targeting the same receptor may have markedly different anticancer activity when used in combinations.…”
Section: Discussionmentioning
confidence: 62%
“…Targeting one gene at a time for both cell cycle genes and RAS genes (other than KRAS G12C for which specific effective inhibitors are now in clinical trials (17,26,27,32)) has shown limited clinical efficacy. (13,33) Moreover, about 30% of tumors with RAS mutations are reported to have co-alterations in cell cycle genes, and about 5.5% of patients with diverse cancer harbor alterations in both BRAF/KRAS and cell cycle genes (136/2457) patients with Foundation Medicine tissue testing (Supplemental Figure 1) which may also explain why targeting only a single pathway can be challenging (14). As reported previously, targeting as many genomic alterations as possible can yield better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…( 16) RAS and RAF alterations can potentially be targeted with drugs that inhibit one of the later steps, including MEK and ERK inhibitors, as well as specific inhibitors of KRAS G12C (for cancers that harbor a specific KRAS G12C mutation). (17,18) Importantly in this regard, we have recently demonstrated that survival was negatively impacted when patients had malignancies that demonstrated alterations in both RAS and cell cycle-associated genes as compared to patients with only one of these pathways altered, (14) and some authors hypothesize that co-targeting MEK and cyclin pathways might be important. (19,20) In an effort to evaluate the clinical impact of a genomic matching combination approach in patients whose advanced tumors harbor both MEK and cell cycle pathway abnormalities, we analyzed individuals who received concomitant MEK inhibitors and CDK inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Such therapies carry clear advantages as they generally lack the systemic side effects of traditional, nontargeted cytotoxic treatment options 4,5 and have revolutionised the outcomes of many malignant conditions. 6,7 NTRK genes code for three trans-membrane tropomyosin receptor kinases (TrkA, B and C) expressed primarily in neural tissue which all play significant roles in the development and function of the nervous system. 8 Activation of TRK by associated neurotrophins leads to phosphorylation of the receptor and activation of downstream cellular processes.…”
Section: Targeting Of Genomic Mutations or Alterations As A Means Of mentioning
confidence: 99%
“…Such therapies carry clear advantages as they generally lack the systemic side effects of traditional, non-targeted cytotoxic treatment options 4,5 and have revolutionised the outcomes of many malignant conditions. 6,7…”
mentioning
confidence: 99%